Model United Nations & Classroom Simulations: What have we learned? - A. Sadri Хуман (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
Model United Nations (MUN) and classroom simulations are common active learning approaches that have been recently discussed in the international relations literature. However, evaluations and critical reflections of these approaches are less common. How do the three traditional liberal arts education (Critical Thinking, Problem Solving, and Improving Communication Skills) are promoted by the MUN techniques? This paper addresses a more reflexive mood to assess what students and professors have learned. This work is based on the author’s experience with the Model United Nations Program (as the faculty advisor and program founder) in addition to knowing the relevant literate of active learning in international relations.